Developing evidence for agricultural and rural development policies and strategies in Nigeria - Salau, Sheu (International Food Policy Research Institute, 2008)
Bridging the research and policy divide remains a top priority on the Nigerian federal government's agenda. This renewed commitment paved the way for the Agricultural Support Facility Project (APSF), which seeks to, among other things, create an environment and produce evidence on specific policy issues facing the Nigerian agricultural sector that allows for a more inclusive design and implementation of evidence-based, pro-poor, gender sensitive, and environmentally sustainable agricultural and rural development policies and strategies in Nigeria. The conviction that the policymaking process should benefit from stakeholders' active participation led APSF to organize a stakeholder workshop to serve as a forum for addressing issues emanating from the evidence being generated by the facility. The workshop objectives were to: share progress on implementing APSF; discuss current research findings; and dialogue with stakeholders on upcoming activities (see Appendix A for Agenda). The workshop brought together participants from the Federal Ministry of Agriculture and Water Resources (FMAWR), the National Planning Commission (NPC), the National Bureau of Statistics (NBS), the Federal Ministry of Finance (FMF), the Federal Ministry of Commerce and Industry (FMCI), the New Partnership for Africa's Development (NEPAD), the donor community, academia, farmers' organizations and the private sector. This executive summary provides an overview of the research findings, highlights key group discussion points, and provides next steps.